COVID-19 Testing Results by HIV Status, March–July 2020, Chicago, USA. (2nd February 2021) - Pyra, Maria; Rusie, Laura; Houlberg, Magda; Balthazar, Christopher; Montgomery, Jerome; Hotton, Anna; Yang, Wenho; Betanzos, Mateo; Green, Maya; Schneider, John
Abstract: The role of HIV in coronavirus disease 2019 acquisition is not yet understood. Among 1862 patients, including 349 people with HIV—with most of these being virally suppressed and 308 having recently used pre-exposure prophylaxis—we compared rates of positive polymerase chain reaction results. Positivity was higher among people with HIV (10.6%) compared with HIV-negative patients (7.1%) but was not significant in adjusted models.